REVITALISASI PERAN MUHAMMADIYAH DALAM BIDANG SOSIAL, PENDIDIKAN, DAN KESEHATAN - Stephy Fitriady Ali; Nuranisa Al Azighah; M. Amin (CV. Adiba Aisha Amira, 2026)
Muhammadiyah is an Islamic movement characterised by renewal (tajdid) which, since its inception, has played an active role in the development of social, educational and health sectors in Indonesia. In line with the dynamics of social change in modern society, it is necessary to revitalise Muhammadiyah's role so that it remains relevant and adaptive to the challenges of the times. This paper aims to examine the revitalisation of Muhammadiyah's role in the social, educational, and health sectors with an emphasis on innovation, empowerment, and institutional strengthening. In the social sector, Muhammadiyah contributes through community service and empowerment oriented towards welfare and independence. In the education sector, Muhammadiyah acts as an agent of renewal by developing modern, holistic Islamic education that is responsive to technological developments. Meanwhile, in the health sector, Muhammadiyah provides health services that integrate Islamic values and medical professionalism. Revitalising Muhammadiyah's role in these three areas is an important strategy for strengthening its tangible contribution to building a progressive Islamic society with social justice.